Migration and Irregular Work in Austria A Case Study of the Structure and Dynamics of Irregular Foreign Employment in Europe at the Beginning of the 21st Century - Jandl, Michael (IMISCoe Reports, 2008)
This meticulously researched study of irregular migrant work in Austria holds many broader lessons for countries all over Europe. The book derives many of its fascinating insights from systematic in-depth interviews with migrants themselves. The authors demonstrate that it is no longer enough to divide the world of foreign employment into "legal" and "illegal" work. Instead, over the past few years, particularly in the context of progressive EU-enlargement in Europe, new manifestations of "irregular migrant work" have evolved. Moreover, the authors convincingly argue that irregular migrant work is based on both supply and demand, and is therefore unlikely to fade away in the foreseeable future.